Organic synthesis toward small-molecule probes and drugs - Schreiber, Stuart L (Proceedings of the National Academy of Sciences - PNAS, 2011)
"Organic synthesis" is a compound-creating activity often focused on biologically active small molecules. This special issue of PNAS explores innovations and trends in the field that are enabling the synthesis of new types of small-molecule probes and drugs. This perspective article frames the research described in the special issue but also explores how these modern capabilities can both foster a new and more extensive view of basic research in the academy and promote the linkage of life-science research to the discovery of novel types of small-molecule therapeutics [Schreiber SL (2009) Chem Bio Chem 10:26-29]. This new view of basic research aims to bridge the chasm between basic scientific discoveries in life sciences and new drugs that treat the root cause of human disease--recently referred to as the "valley of death" for drug discovery. This perspective article describes new roles that modern organic chemistry will need to play in overcoming this challenge.